Dampak Donor MDGs terhadap Pembangunan Ekonomi dan Politik di Indonesia: Analisis Kontemporer - Efendi, Tifani; Magriasti, Lince (Medan Resource Center, 2024)
This study examines the impact of Millennium Development Goals (MDGs) donors on Indonesia's economic and political development through a contemporary analysis. The research investigates how international aid from MDGs donors has influenced Indonesia's economic growth and political dynamics, addressing the core question of the effectiveness and sustainability of such aid. The methodology employs a qualitative approach, utilizing case studies, in-depth interviews with key stakeholders, and analysis of relevant policy documents. Findings reveal that while MDGs donors significantly contributed to economic development, the effectiveness of the aid was often compromised by political factors such as governance issues and policy inconsistencies. The study concludes that the integration of international aid into national policies requires a more strategic approach to enhance both economic and political outcomes. This research highlights the necessity for adaptive strategies and improved coordination between international donors and local governments to ensure sustainable development.